Guan Yu : blood brothers to the end : a Chinese legend - Jolley, Dan (Graphic myths and legends., 2008)
A graphic novel adaptation of the legend of second-century Chinese warrior Guan Yu, who battles the Yellow Scarves with his blood brothers by his side only to be faced with even more threatening foes.